(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study consisted of 3 variants. According to the results obtained from the research, in the control (dry) version treated with 0.001% solution of "Violet K", the mortality rate due to disease agents was 53.30% in the caterpillars of the Vatan breed, while in the "Sverico-yellow" breed it was 41.70%, and in the "Oragase" breed it was 17.00%. The mortality rate of the first experimental variant was 12.50% in the "Vatan" breed, 15.20% in the "Sverico-yellow" breed, and 6.70% in the "Oragase" breed. In the second control (aqueous) variant, 23.50% mortality was observed in the Sverico-yellow breed, and 8.00% in the Oragase breed, but no mortality occurred in the "Vatan" breed. According to the weight of the silk coat, the weight of the cocoon of the "Vatan" breed in the control (dry) variant was 235.7 mg, 138.2 mg in the "Sverico-yellow" breed, and 218 mg in the "Oragase" breed. The amount of the control (aqueous) variant was 340.5 mg in the "Vatan" breed, 173.5 mg in the "Sverico-yellow" breed, and 139.5 mg in the "Oragase" breed. In the experimental version, the weight of the silk coat of the "Vatan" breed was 460.5 mg, 160.5 mg in "Sverico-yellow", and 169 mg in "Oragase". In the productivity of butterflies, the number of eggs in the "Vatan" breed was 300 in the control (dry) version, 265 in the control (aqueous) version, and 1,471 in the experimental version. In the "Sverico-yellow" breed, there were 270 eggs in the control (dry) variant, 306 eggs in the control (aqueous) breed, and 1235 eggs in the experimental breed. In the "Oragase" breed, the number of eggs was 239 in the control (dry) variant, 602 in the control (aqueous) variant, and 589 in the experimental variant. Scientific innovation. Scientific innovation in the research works conducted in the direction of solving 2 problems in the relevant cocoon farms was the development of methods of prevention and elimination of diseases recorded in the eggs and caterpillars of the mulberry silkworm, as well as methods of increasing the viability of eggs and caterpillars.